USE OF STABLE ISOTOPES IN THE DETERMINATION OF THE MEAN ALTITUDE OF RECHARGE AND THE INVESTIGATION OF FUNCTION MECHANISM OF SPRING WATERS IN ARGOLIS PENINSULA (GREECE) - Matiatos, I.; Alexopoulos, A.; Zouridakis, N. (Bulletin of the Geological Society of Greece, 2010)
In the present study, the isotopic composition (δ18Ο) of several spring waters in Argolis peninsula is examined. The use of the specific isotope aimed at the determination of the altitude of recharge areas, while the credibility of the extracted results was verified by in situ geological observations. The applied methodology included the construction of a linear diagram which correlates the stable isotopic values (δ18Ο) in meteoric waters and the altitude. Isotopic data, concerning meteoric waters, came from: a) rain gauge stations of GNIP network (IAEA/WMO), b) rain tanks and selected wells located in Mt. Arachnaio, c) improvised rain collectors which were put in several sites in the peninsula. A decrease of 0.45‰ δ18Ο per 100m altitude was determined. The average isotopic composition of the examined springs, as far as δ18Ο is concerned, resulted from 14 sampling periods between October 2005 and March 2008. This 18O-content of spring waters was used to derive the recharge area and consequently to evaluate the mechanism of water renewal.